Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.est.9b03763
|View full text |Cite
|
Sign up to set email alerts
|

Role of Digestate and Biochar in Carbon-Negative Bioenergy

Abstract: Digestate and biochar can be land applied to sequester carbon and improve net primary productivity, but the achievable scale is tied to expected growth in bioenergy production and land available for application. We use an attributional life-cycle assessment approach to estimate the greenhouse gas (GHG) emissions and carbon storage potential of biochar, digested solids, and composted digested solids generated from organic waste in California as a test case. Our scenarios characterize changes in organic waste pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…C-rich organic amendments (e.g. biochar) with a potential to sequester C [ 7 ] could be applied together with digestate and compensate this disadvantage by higher stabilization of both C [ 8 ] and N [ 9 ]. It was reported that amendment of digestate and biochar increased both total organic carbon (TOC) and soil C turnover in comparison to the sole digestate application [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…C-rich organic amendments (e.g. biochar) with a potential to sequester C [ 7 ] could be applied together with digestate and compensate this disadvantage by higher stabilization of both C [ 8 ] and N [ 9 ]. It was reported that amendment of digestate and biochar increased both total organic carbon (TOC) and soil C turnover in comparison to the sole digestate application [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies confirm the positive effect of biogas systems and digestate application on SOC formation in general (Breunig, Amirebrahimi, Smith, & Scown, 2019; Franko & Witing, 2020; O'Keeffe et al., 2019; Prays & Franko, 2018; Witing et al., 2018). Studies comparing residue incorporation and biogas digestate application report a higher SOC formation in the latter case (Chen et al., 2012; Nielsen et al., 2020).…”
Section: Discussionmentioning
confidence: 75%
“…The flux measured from the CRDS is in gas units using equation (1), which is then converted into mass concentration (mg/time) using the Ideal Gas Law in equation (2). We converted J to calculate the cumulative emissions to mass/g soil basis.…”
Section: Flux Measurements and Calculationsmentioning
confidence: 99%
“…For this study, we examined the impact of supplementing the traditional land application of manure with anaerobic digestate (AD) on soil GHG emissions of CO2 and N2O. AD is the decomposition process of organic matter without the presence of oxygen 2 . It is low in carbon, nutrient-rich, and may increase net primary productivity of crops and increase carbon sequestration in soils 3 .…”
Section: Introductionmentioning
confidence: 99%